The role of satisfaction on labor diaspora dynamics: an analysis of entry and exit of Portuguese nurses - Elo, Maria (2021)
Psychology and management has acknowledged the effect of satisfaction, but in diaspora research the role that satisfaction plays in international mobility is understood mainly on economic macro-level. However, when labor diasporas, economic clusters and other hot spots emerge, they are not following only economic indicators but also individual level drivers. International migration consists of mobile individuals who decide when and where to enter and why to leave while the infrastructure and institutional framework provide the settings for their decision making and comparison. Pull and push forces have been identified, but their explanatory power is more dominant during the preand nascent phases of migration. A good example of this movement is Portugal, a peripheral European country, recently intervened by IMF that suffered the deepest effects of Great Financial Crisis (GFC), namely in a specific professional group: nurses. What makes Portuguese nurses to leave their country and become labor diaspora and stay labor diaspora? This explorative qualitative study is among the first that focuses on the role of satisfaction and its effects on labor diaspora mobility and stability. The findings illustrate that satisfaction relates to good working conditions and wages, but also to the possibilities to communicate with locals and other diasporans, and to the family situation. When this perceived satisfaction is lower than the expected satisfaction after migration the probability of migration is high, but when the difference is inexistent or negative migration will not take place. The study contributes to the discussion on contemporary labor diaspora and brain circulation. It provides in-depth understanding to the dynamics of this form of labor diaspora from empirical research and provides propositions and suggestions for future research.